TEMPAT CUCI TANGAN OTOMATIS MENGGUNAKAN SENSOR INFRARED OBSTACLE AVOIDANCE - Habib, Muhammad Habib Khoir; Nur Wahid, Syamsudin (Universitas Islam Balitar Blitar, 2024)
When the Covid-19 virus developed in Wuhan and spread throughout the world, efforts to prevent the spread of the Covid-19 virus were carried out using the 3M Protocol, washing hands, using masks, using sanitizers. One step to overcome this is to create an automatic hand washing tool. It is hoped that making this simple tool can reduce the spread of the Covid-19 virus in any region. The simple tools and materials make it possible for most people to make it. However, after testing, this tool still has shortcomings and errors may occur. This can still be overcome with slight modifications by giving it a slightly dark color by painting or placing the sensor behind the small faucet stop. The hand washing device using IR obstacle avoidance is placed in the sink in the faucet and liquid soap container. The equipment created can detect hands from a distance of 2.5 cm to 30 cm and can dispense water and soap when an obstacle is detected. So the use of the Infrared Obstacle Avoidance sensor in the hand washing place can operate properly as it should.